The Nature of Psycholinguistics: A Multidimensional Perspective on Language and Mind - Kristina Natalia Sidauruk; Bernieke Anggita Ristia Damanik (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Psycholinguistics explores the complex relationship between language and cognition. The study of how language is acquired, processed, and produced involves various cognitive mechanisms and neural processes. This paper examines these mechanisms, focusing on the intersection of cognitive science, linguistics, and psychology, and the ways culture and technology shape linguistic behaviors. It also discusses the application of psycholinguistics in education, clinical therapy, and artificial intelligence (AI). Findings underscore the importance of psycholinguistics in addressing challenges posed by multilingualism, globalization, and digital communication tools. Highlight the importance of integrating AI-based technology to support psycholinguistic studies, such as using machine learning for language analysis. Emphasize the relevance of psycholinguistics in supporting language learning in the globalization era, particularly in multilingual education contexts